Pengaruh Green Accounting, Kinerja Lingkungan, Pertumbuhan Laba dan Corporate Social Responsibility terhadap Nilai Perusahaan - Fitriana, Nur; Harefa, Chandwiman Anugerah; Daulay, Sangra Puttidia; ., Fajar; Putra, Eldo Maha (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to examine the influence of Green Accounting, Environmental Performance, Profit Growth, and Corporate Social Responsibility (CSR) on firm value. With increasing global competition, companies face challenges to enhance their value by considering environmental sustainability and social responsibility. Green Accounting functions as a tool to manage environmental costs, while environmental performance is measured through corporate compliance with regulations such as PROPER. Profit growth reflects the financial performance of a company, whereas CSR represents the company’s commitment to the environment and society. This study employs a descriptive qualitative method with literature analysis, incorporating secondary data from various previous studies. The results indicate that these factors have varying effects on firm value, with some studies showing positive, negative, or insignificant influences. Therefore, further research is needed to clarify the relationship between these factors and firm value